Comparison of referring and final pathology for patients with T‐cell lymphoma in the National Comprehensive Cancer Network. Issue 13 (4th April 2014) - Herrera, Alex F.; Crosby‐Thompson, Allison; Friedberg, Jonathan W.; Abel, Gregory A.; Czuczman, Myron S.; Gordon, Leo I.; Kaminski, Mark S.; Millenson, Michael M.; Nademanee, Auayporn P.; Niland, Joyce C.; Rodig, Scott J.; Rodriguez, Maria A.; et al.
Abstract : BACKGROUND: T‐cell lymphomas (TCLs) are uncommon in the United States. The accurate diagnosis of TCL is challenging and requires morphologic interpretation, immunophenotyping, and molecular techniques. The authors compared pathologic diagnoses at referring centers with diagnoses from expert hematopathology review to determine concordance rates and to characterize the usefulness of second‐opinion pathology review for TCL. METHODS: Patients in the National Comprehensive Cancer Network non‐Hodgkin lymphoma database with peripheral TCL, not otherwise specified (PTCL‐NOS), angioimmunoblastic TCL (AITL), and anaplastic lymphoma kinase (ALK)‐positive and ALK‐negative anaplastic large cell lymphoma (ALCL) were eligible if they had prior tissue specimens examined at a referring institution. Pathologic concordance was evaluated using available pathology and diagnostic testing reports and provider progress notes. The etiology of discordance and the potential impact on treatment were examined. RESULTS: Among 131 eligible patients, 57 (44%) had concordant results, totaling 64% of the 89 patients who were referred with a final diagnosis. Thirty‐two patients (24%) had discordant results, representing 36% of those who were referred with a final diagnosis. The rates of discordance among patients with of PTCL‐NOS, AITL, ALK‐negative ALCL, and ALK‐positive ALCL were 19%, 33%, 34%, and 6%, respectively. In 14 patients (44% of discordant results), pathologic reclassification could have resulted in a different therapeutic strategy. Forty‐two patients (32%) were referred for classification with a provisional diagnosis. CONCLUSIONS: In a large cohort of patients with TCL who were referred to National Comprehensive Cancer Network centers, the likelihood of a concordant final diagnosis at a referring institution was low. As current and future therapies target TCL subsets, these data suggest that patients with suspected TCLs would benefit from evaluation by an expert hematopathologist. Cancer 2014;120:1993–1999 . © 2014 American Cancer Society . Abstract : A high discordance rate was observed between referring diagnoses and expert hematopathology review of T‐cell lymphomas. In 1 in 10 patients, expert review resulted in a pathologic reclassification that may have impacted treatment.